An analysis of context-based similarity tasks in textbooks from Brazil and the United States - Barcelos Amaral, Rúbia [UNESP]; Hollebrands, Karen (Taylor & Francis, 2017)
Three textbooks from Brazil and three textbooks from the United States were analysed with a focus on similarity and context-based tasks. Students’ opportunities to learn similarity were examined by considering whether students were provided context-based tasks of high cognitive demand and whether those tasks included missing or superfluous information. Although books in the United States included more tasks, the proportion of tasks focused on similarity were about the same. Context-based similarity tasks accounted for 9%–29% of the similarity tasks, and many of these contextual tasks were of low cognitive demand. In addition, the types of contexts that were included in the textbooks were critiqued and examples provided.
Keywords: Context-based problems; similarity; tasks; textbook